A Reply to Pierotti’s (2018) Review of “Evolutionary Ethnobiology”: Decolonizing Latin American Science - Albuquerque, Ulysses Paulino; Ferreira Júnior, Washington Soares; Vandebroek, Ina; Bussmann, Rainer W.; Paniagua-Zambrana, Narel Y.; Ladio, Ana H.; Voeks, Robert; Melo, Felipe; Jacob, Michelle C. M.; Gonçalves-Souza, Thiago; Lopes, Ariadna Valentina; Soldati, Gustavo Taboada (Ethnobiology Letters, 2021)